2022
DOI: 10.1002/ange.202211552
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo‐Designed Type 3 Copper Protein Tunes Catechol Substrate Recognition and Reactivity

Abstract: De novo metalloprotein design is a remarkable approach to shape protein scaffolds toward specific functions. Here, we report the design and characterization of Due Rame 1 (DR1), a de novo designed protein housing a di‐copper site and mimicking the Type 3 (T3) copper‐containing polyphenol oxidases (PPOs). To achieve this goal, we hierarchically designed the first and the second di‐metal coordination spheres to engineer the di‐copper site into a simple four‐helix bundle scaffold. Spectroscopic, thermodynamic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The formation of larger assemblies for FDH/AlaDH@S-CAB C may be originated by the covalent nature of the disulfide staple that shifts the equilibrium towards higher ordered assemblies as illustrated in Figure 5d. In contrast, FDH/AlaDH@SCAB H assemblies are mediated by weaker non-covalent interactions dominated by the equilibrium with a K D in the order of μM for copper:bihistidine interactions (Pirro et al, 2023), which, as shown experimentally results in discrete assemblies.…”
Section: Catalytic Activity and Biosynthesis Of L-alanine Of Scaffold...mentioning
confidence: 74%
“…The formation of larger assemblies for FDH/AlaDH@S-CAB C may be originated by the covalent nature of the disulfide staple that shifts the equilibrium towards higher ordered assemblies as illustrated in Figure 5d. In contrast, FDH/AlaDH@SCAB H assemblies are mediated by weaker non-covalent interactions dominated by the equilibrium with a K D in the order of μM for copper:bihistidine interactions (Pirro et al, 2023), which, as shown experimentally results in discrete assemblies.…”
Section: Catalytic Activity and Biosynthesis Of L-alanine Of Scaffold...mentioning
confidence: 74%
“…This theoretical scheme has already been tested and successfully adopted in previous DFT investigations carried out in our laboratory on various bioinorganic copper systems. [72][73][74]…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, recent success has been achieved in creating functional arti cial metalloenzymes (ArMs) within de-novo scaffolds. [39][40][41][42][43][44][45][46][47][48] One such example is the novo-designed arti cial Cu proteins (ArCuPs) that function as peroxidases and peroxygenases featuring Cu(His) 3 active sites within trimeric (3SCC) self-assemblies. 45,46 The 3SCC ArCuP activates H 2 O 2 45 and electrocatalyzes the 2eand 4eoxidation and peroxygenation.…”
Section: Introductionmentioning
confidence: 99%